WINTER WHEAT (TRITICUM AESTIVUM L.) MUTAGENIC DEPRESSION UNDER GAMMA-RAYS ACTION - Nazarenko, M. M. (Scientific Progress & Innovations, 2021)
The purpose of our investigation was to identify the peculiarities of depressive consequences of the after-effect of different gamma-rays doses on locally bred winter wheat varieties as to the indicators of germina-tion, survival, morphometry, and yield. The parameters of germination and survival, the cause of the main ontogenesis phases in winter wheat plants of local varieties (Komertsiina and Spivanka) in the first genera-tion were studied. The influence of mutagenic depression on yield structure indices (morphometry of mature plants) was established and the level of their variability was estimated too. In 2019–2020, the experiments were conducted in the experimental fields of the research center of Dnipro State Agrarian and Economic University. The seeds of Spivanka and Komertciina varieties, irradiated with gamma rays in doses of 100, 150, 200, 250, 300 Gy were used in the experiments. Dry seeds were the control. It was found that the highest depression concerning all the studied characteristics were manifested in Spivanka variety, except for the dose of 250 Gy, which indicated the specificity of the interaction of gamma-rays depressive activity with the genotypes of certain varieties and the complex nature of depressive effects development at the plant or-ganism level. The most informative parameters of mutagenic depression in M1 plant generation of soft winter wheat varieties were: germination and survival rate of plants, pollen fertility and such yield structure pa-rameters as plant height, grain weight from the main spike, and thousand-kernel weight. All of these parame-ters having a high level of significance are connected with the mutagen dose rate. The genotypes of locally bred varieties (Komertciina and Spivanka) turned out to be highly sensitive to gamma-rays action, which was manifested in the semi-lethality at even initial, moderate doses (100 Gy). Variance analysis showed that mutagen dose factor first of all affected the formation of yield structure indicators, then the genotype of the original variety. It has been found that there may be a rapid decrease in separate parameters in the first generation at reaching certain dose limits. Moreover, these doses are determined by the genotype of the sub-ject of mutagenic action.